2007
DOI: 10.1097/01.ccm.0000254335.88023.0e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic sepsis on the voltage-gated sodium channel in isolated rat muscle fibers*

Abstract: Chronic inflammation and sepsis induced modifications of sodium channel properties that could contribute to muscular inexcitability. This inexcitability can be elicited by a modification of properties or type of voltage-gated sodium channels. Our results lead us to explain this inexcitability by an up-regulation of NaV 1.5 sodium channel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…In steroid-treated, denervated rat muscle, it was found that a combination of depolarization of the resting potential and a hyperpolarized shift in the voltage dependence of sodium channel inactivation resulted in unexcitability of the majority of muscle fibers (196, 580 -582). The voltage dependence of sodium channel inactivation was also found to be shifted in the hyperpolarized direction by pure sepsis in the rat (594). These data suggest that increased inactivation of sodium channels is a major contributor to reduced excitability.…”
Section: B "Sodium Channelopathy" In Muscle Inmentioning
confidence: 71%
See 1 more Smart Citation
“…In steroid-treated, denervated rat muscle, it was found that a combination of depolarization of the resting potential and a hyperpolarized shift in the voltage dependence of sodium channel inactivation resulted in unexcitability of the majority of muscle fibers (196, 580 -582). The voltage dependence of sodium channel inactivation was also found to be shifted in the hyperpolarized direction by pure sepsis in the rat (594). These data suggest that increased inactivation of sodium channels is a major contributor to reduced excitability.…”
Section: B "Sodium Channelopathy" In Muscle Inmentioning
confidence: 71%
“…In innervated mature skeletal muscle, only the Na v 1.4 sodium channel isoform is expressed. After denervation, steroid treatment, or sepsis, there is upregulation of the Na v 1.5 isoform (578,594,789). Normally, the Na v 1.5 isoform is expressed in embryonic skeletal muscle but is downregulated during development (790).…”
Section: B "Sodium Channelopathy" In Muscle Inmentioning
confidence: 99%
“…Not all fibres are affected to the same extent and the percentage affected determines the severity of weakness [17]. Increased NaV1.5 has also been shown in a model of chronic sepsis in rats [103] and lipopolysaccharide interaction with and disruption of the channel has been demonstrated in vitro [104]. However, these effects have yet to be shown in ICUAW muscle.…”
Section: Electrical Inexcitabilitymentioning
confidence: 99%
“…Upregulation of NaV1.5 sodium channels has been demonstrated in the muscle of rats with chronic sepsis, suggesting that several risk factors lead to muscle electrical nonexcitability [79]. A negative shift in sodium channel gating in peripheral nerves of muscle is distinguished from CIM as a characteristic disorder in CIP [80].…”
Section: Physical Disabilities -Therapeutic Implicationsmentioning
confidence: 99%